(untitled) - Katsumata, S. (Tokyo, 1937)
First published in 1937 this is a collection of articles written by the author under the pseudonym 'Waseda Eisaku' for the Japan Tourist Bureau's magazine over twenty five years.
Keywords: Nhật Bản,Japan; Mô tả và du hành,Description and travel